HEALTH PROMOTION IN IMPROVING HEALTHY LIVING BEHAVIORS IN THE COMMUNITIES OF SUCOPANGEPOK VILLAGE, JEMBER REGENCY - Wakit, Saipul; Terry Ana Fauziyah; Maylanda, Osera (Universitas Airlangga, 2024)
Hypertension is a symptom of high blood pressure in a person. This condition causes many cases that put sufferers at risk. In Indonesia, hypertension cases are quite high and many people suffer from them. So, to overcome and prevent, practical and preventive steps are needed, including providing early education and prevention for the community to avoid the impacts caused by hypertension. These efforts are carried out through community empowerment activities through health promotion. The activity was carried out in Sukogepok village, Jember district, with the target of the activity being housewives. The aim is to identify the prevalence of people suffering from hypertension. The method used in this activity includes three stages, namely through preparation, implementation and evaluation. The implementation technique is to provide material to increase knowledge about hypertension, symptoms and efforts to prevent it. Practically, this is done through lectures, discussions, questions and answers and carrying out blood pressure checks on people who attend the activity. Blood pressure checks are carried out before and after the activity. The results show an increase in knowledge about hypertension, causes and prevention efforts. The results of the examination showed that around 35 people had high blood pressure who were categorized as hypertension.